The comparison of algorithms in change-points problem. - Chang, Kuo-Ching (Journal of Applied Science and Engineering)
A fast two stage (TS) algorithm by window method is proposed. First, we apply the window method by using the log-likelihood ratio measure to find a subset of candidate change-points; and use dynamic programming (DP) algorithm on the chosen subset to obtain good initial change-points which will be proximate to the locations of the true change-points. Secondary, the segmental K-means (SKM) algorithm is applied on the initial change-points obtained in the first stage. Some simulated data sets are investigated for four algorithms and the results show that our algorithm works very well. In the comparison of CPU times, our TS algorithm is fast and can be up to 19.07 times than the speed of DP algorithm.